(untitled) (Journal of Monno Medical College, 2023)
Background: Bangladesh is a country with high prevalence of smoking which is a contributing factor to cause respiratory diseases. The situation of COVID-19 has become threatening physically for smokers as it is also a respiratory related disease and it can also help altering smoking behaviour because of perception towards this pandemic. Objective: The objectives of this study were to investigate changes in cigarette smoking behaviour during COVID-19 among the adult smokers of Bangladesh according to perception towards COVID-19, and assess association between changes in cigarette smoking behaviour and perception towards COVID-19. Methodology: An online descriptive cross-sectional study was conducted during 16 April, 2021 to 30 April, 2021 using anonymous Google form. Only adult Bangladeshi cigarette smokers were included in this study. Descriptive and co-relational analyses were conducted using SPSS-28.0. Results: Among 373 valid responses, 259(69.43%) reported change in smoking behaviour during COVID-19. Some 313(83.91%) cigarette smokers perceived risk of being infected by COVID-19 and 30(8.04%) smokers were infected by COVID-19. Many (187, 50.13%) participants perceived that smokers have higher risk of contracting infection. In addition, 292(78.28%) smokers believed that smoking can cause more complications if infected, 182(48.79%) felt worried about their smoking behaviour and 225(60.32%) participants thought of lessening smoking during COVID-19. Majority (229, 61.39%) of the respondents tried to quit smoking. Patterns of change in cigarette smoking during COVID-19 were significantly associated with both perceived risks of higher contractibility (p=.001) and higher physical complications (p=.004). Conclusion: Percentage of people with changed smoking behaviour during COVID-19 was very high. Perception towards adverse impact of COVID-19 on smoking behaviour may lead to this change. Journal of Monno Medical College, June 2023; 9 (1): 24-29